1999
DOI: 10.1016/s0002-9440(10)65182-6
|View full text |Cite
|
Sign up to set email alerts
|

Hemoxygenase and Nitric Oxide Synthase Do Not Maintain Human Uterine Quiescence during Pregnancy

Abstract: The nitric oxide (NO)-cGMP pathway has been proposed as a mechanism for relaxation of myometrium during pregnancy and as a modulator of labor. Carbon monoxide (CO) , produced by hemeoxygenases (HO-1 and HO-2) , also activates soluble guanylate cyclase to increase cGMP. A recent study reported a large increase in HO-1 and HO-2 proteins during pregnancy , suggesting that the HO-CO pathway may be important in the maintenance of uterine quiescence during pregnancy. In this study we used Western blotting , reverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…This suggests that either iNOS is absent or is present in such low quantities, expressed only by certain cell types in the uterus, that it was below the detection threshold by Western analysis. This is in agreement with a previous report regarding lack of expression of iNOS protein in the human myometrium, in both the pregnant and in the nonpregnant state [38], where the authors conclude that uterine quiescence during pregnancy is not maintained by NOS activity. Similarly, the myometrium from pregnant rats is not sensitive to relaxation by cGMP, probably due to reduced expression of cGMP-dependent protein kinase [39].…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that either iNOS is absent or is present in such low quantities, expressed only by certain cell types in the uterus, that it was below the detection threshold by Western analysis. This is in agreement with a previous report regarding lack of expression of iNOS protein in the human myometrium, in both the pregnant and in the nonpregnant state [38], where the authors conclude that uterine quiescence during pregnancy is not maintained by NOS activity. Similarly, the myometrium from pregnant rats is not sensitive to relaxation by cGMP, probably due to reduced expression of cGMP-dependent protein kinase [39].…”
Section: Discussionsupporting
confidence: 93%
“…Acevedo and Ahmed [18] postulated the HO-CO system as an endogenous tocolytic agent in human myometrium during pregnancy, but Barber et al [39] did not observed an increment of HO expression in human pregnancy, suggesting that the CO pathway is not involved in uterine quiescence or contractility in labor. Our results suggest that CO via cGMP could be implicated in uterine quiescence since two specific HO inhibitors significantly decreased uterine cGMP accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both the spontaneous and oxytocin-induced contractions of myometrial strips were inhibited by hemin injection (Acevedo and Ahmed, 1998;Longo et al, 1999). Contradictory reports showed that HO-1 and HO-2 were not up-regulated during pregnancy in myometrium at all (Barber et al, 1999). Therefore, role of the HO/CO system in maintaining uterine quiescence during pregnancy is still not settled.…”
Section: Carbon Monoxide and Reproductive Systemmentioning
confidence: 98%